AB0190 Synovial fluid derived invariant natural killer T cells in chronic arthritides show an increased programmed death-1 expression and anergic phenotype. (23rd January 2014) - Venken, K.; Melis, L.; Jacques, P.; Van Praet, L.; De Bock, W.; Piette, Y.; van den Bosch, F.; Verbruggen, G.; Elewaut, D.
Abstract : Background: One potential factor for chronicity in arthritides such as rheumatoid arthritis (RA) and spondyloarthritis (SpA) is a suboptimal feedback by regulatory T cells. invariant Natural Killer T (iNKT) cells are a prototypic regulatory T cell subset that recognize glycolipids presented by CD1d on Antigen Presenting Cells. They have the capacity to secrete copious amounts of cytokines, thereby influencing various immune responses. Earlier work demonstrated the regulatory capacity of iNKT cells in a murine model of gut and joint inflammation in SpA (1). However, little is known on human iNKT cells in human arthritides. Objectives: In this study, we aimed to evaluate the iNKT cell frequency, phenotype and glycolipid reactivity in the periphery and at the site of inflammation in chronic arthritis patients. Methods: We have analyzed the frequency and phenotype of iNKT cells in peripheral blood (PB) and paired synovial fluid (SF) in a cohort of 16 RA and 18 SpA patients and 20 healthy individuals (only PB) by flow cytometry using the iNKT specific antibody 6B11. As an additional control group for the synovial compartment we included 10 patients with gouty arthritis. To test iNKT cell reactivity, PB and SF mononuclear cells (MC) of RA and SpA patients were cultured in the presence of the prototypical iNKT ligand α-GalCer or bacterial iNKT ligands (diacylglycerols derived from Borrelia burgdorferi and Streptococcus pneumonia ) Results: Our data demonstrate a reduced number of iNKT cells in PB of RA and SpA patients as compared to healthy controls. By contrast, iNKT cell numbers were significantly increased in SF versus PB of RA and SpA patients. Interestingly, this was not observed in SF from gouty arthritis patients. In general, α-GalCer induced iNKT cell expansion in SFMC from arthritis patients was lower as compared to PBMC cells. Remarkably, in some patients, SF opposed to PB iNKT cells responded towards bacterial iNKT ligands. As infections have been associated with development of joint inflammation, especially in SpA, this is of particular interest and suggests a differential antigen reactivity in synovial fluid as opposed to circulating iNKT cells. Phenotypical analyses indicated that an increased number of iNKT cells in the SF of RA and SpA patients but not gouty patients, expressed Programmed Death-1 (PD-1), a co-inhibitory receptor. In mice, iNKT cells rapidly up-regulate PD-1 upon antigenic stimulation which led to induction of iNKT cell anergy (2). In our human PBMC cultures, PD-1 levels on iNKT cells also increased upon α-GalCer stimulation and this was related to the magnitude of the proliferative response. Moreover, SFMC of chronic arthritis patients showed increased responses towards α-GalCer in the presence of PD-1 neutralizing antibodies. Conclusions: Our data suggest a disease associated mechanism of iNKT cell activation in the inflamed joint of chronic but not acute forms of arthritis. Strikingly, iNKT cells within synovial cavity differ substantially from circulating cells in antigen reactivity, proliferative response and induction of PD-1. Overall, the findings highlight a particular role of iNKT cells in TNF driven forms of arthritis. References: Jacques P. et al. Arthritis Rheum. 2010;62(4):988-99. Parekh V et al. J Immunol. 2009;182(5):2816-26. Disclosure of Interest: None Declared